Prototype Design of Delta Wye Starting System for Laboratory-based 3-Phase Induction Motor - Suryani; Marupah (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
Electric motors with electromagnetic devices that convert electrical energy into mechanical energy, so it can be that electric motors are included in the category of dynamic electric machines. The research aims to find out the design of the circuit form prototype from wye-delta, how to replace the system control circuit starting wye-delta, and obtain a significant result measuring the flowing current of the 3-phase induction motor when the motor starts the motor running. The method used in another study of literature is to design and test tools and data retrieval. The system test results are compelling, obtained, digging, initial current, electric motor with value, with the acquisition of measurement results when using the wye system on R, S, and T phase each 0,6 ampere, 0,8 ampere, and 0,6 ampere. When using the delta system on the R phase of 7,5 ampere, S phase of 8,5 ampere, and T phase of 8,3 ampere. Prototypes from these tools operate with a controller system, using a tool called a semiautomatic control system, with an electromagnetic working principle where the primary function of the contactor is a magnetic switch.